(untitled) (International Journal of Banking and Finance, 2022)
This study investigates whether the COVID-19 pandemic has caused asset price bubbles in the stock and oil markets in the United States and Malaysia. More specifically, the study seeks to detect the onset and end of possible speculative bubbles and their causes in these markets. It also examines the existence of a contagion effect between the stock and oil markets during the Covid-19 pandemic. To achieve these objectives, the study used the Generalized SADF (GSADF) developed by Phillips et al. (2015) in order to check for existence of bubbles within the time frame from January 1, 2020, to April 24,2020. This technique allows one to look for the occurrence of multiple bubbles during the sample period with great precision. The findings showed that five out of the six equities, including the oil price indices had multiple bubbles. Evidence was also obtained which linked the explosive activity episodes between the crude oil market and the US stock markets from the start and end point of each bubble event. These findings add not only to the literature on the existence of bubbles in the financial and energy markets during the initial outbreak of COVID-19, but also to the significance of the negative impact of pandemics on bubble contagion effects under extreme market conditions.